BUDAYA ORGANISASI DAN KINERJA PERAWAT DI PUSKESMAS KOTA DAN PUSKESMAS KABUPATEN - Syafrisar Meri Agritubella; Idayanti Idayanti; Rusherina Rusherina (Fakultas Keperawatan, Universitas Riau, 2022)
Organizational culture is a habit that becomes a social force that can move individuals to do work and is a characteristic of an organization. Organizational cultur is a reflection of the daily activities carried out by nurses to effectively and efficiently. The purpose of the study was to examine the relationship between organizational culture and the performnance of nurses at the City and in the regions. This research is a quantitative research with cross sectional study. The population is all nurses, with a total sample technique obtained a total sample of30 people. Collecting data using a questionnaire on organizational culture and nurse performance. Data analysis using Chi-Square Test. The tesults showed that there was no relationship between organizational culture and the performance of nurse in the city and in the regions. Recommendation: leaders can evaluate the performance of nurses through internal meetings and build a conducive organizational culture and the need for management developtment to improve better performance.